Adsorptive removal of multiple organic dyes from wastewater using regenerative microporous carbon: Decisive role of surface-active sites, charge and size of dye molecules. (December 2022) - Joshi, Pratiksha; Prolta, Abeena; Mehta, Sweta; Khan, Tuhin Suvra; Srivastava, Manoj; Khatri, Om P.
Abstract: Present work addresses the synthesis of microporous activated carbon (SDAC) by a facile thermochemical conversion of teak sawdust powder. The high surface area (1999 m 2  g −1 ), excellent microporosity (average pore size: 2.62 nm), and turbostratic carbon structure with intertwined graphitic domains make SDAC a highly efficient adsorptive material for the removal of organic pollutants. The spectroscopic analyses (FTIR, Raman, and XPS) and adsorption locator calculations revealed multiple interactions between organic dyes and SDAC adsorbent, i.e., electrostatic, π-π, n-π interactions, and hydrogen linkages. The size, chemical functionalities, aromatic rings, electronegative and heteroatoms in dye molecules, along with the surface-active sites, microstructured and textural features of SDAC adsorbent collectively governed the interaction pathways and adsorption efficiency. The calculated adsorption energy using Monte Carlo-based simulation annealing method signified faster and higher adsorption of malachite green than methylene blue dye at surface-active sites (-COOH, CO, C–OH, and π-electron-rich domains) of SDAC adsorbent, corroborating the experimental results. The batch-mode adsorptive separation results showed remarkably high adsorption efficiency (>99%) for industrial wastewater to remove cationic and anionic dyes together. The SDAC displayed significantly high adsorption of methylene blue dye (625 mg.g - 1 ) with excellent recyclability without measurable loss of adsorption efficiency even after ten cycles. The SDAC fixed-bed column showed a dye removal capacity of 594 mg.g - 1 at 90% breakthrough in a continuous-mode process signifying its applicability for a real-time industrial run. The excellent conformity between batch mode and fixed bed continuous column adsorption data, along with higher removal capacity and remarkable recyclability, promise the use of SDAC adsorbent for industrial wastewater treatment to remove multiple organic pollutants. Graphical abstract: Image 1 Highlights: High surface area (1999 m 2  g −1 ) activated carbon (SDAC) is prepared by thermochemical activation. Spectroscopic and computational methods revealed multiple adsorptive interaction pathways. Batch-mode and fixed-bed column studies showed high adsorptive removal of organic dyes. Charge and size of organic dyes along with surface-active sites of SDAC govern adsorptive events. SDAC displayed excellent recyclability even after ten cycles.